PENGENDALIAN AIR DAN NUTRISI PADA TANAMAN SELADA HIDROPONIK MENGGUNAKAN KONTROLER PID BERBASIS ARDUINO - Arsyanur Muhammad Erlangga; Fakhriy Hario Partiansyah; Gaguk Asmungi (Jurnal Mahasiswa TEUB, 2023)
Hydroponics is a method of cultivating plants without using soil media. Farming with hydroponic media always pays attention to providing nutrient levels that are in accordance with the needs of plants. The purpose of this research is to test a water and nutrient control system using a PID controller with a setpoint of 500 ppm and 14 cm water level. By using a PID controller, the system produces a small steady state error and gets a faster settling time. The PID controller tuning process using the Ziegler-Nichols 1 method obtained parameter values Kp = 8.4, Ki = 0.15, and Kd = 21. From the test results of nutrient control, it was found that the steady state occurred at the 45th second, overshoot 0% and steady state error was 2.53%. From the results of the water level control test, it is obtained that the steady state occurs at the 175th second, the overshoot is 0% and the steady state error is 0.36%. Index Terms— Hydroponics, PID Controller, Water and Nutrient Control.